2005
DOI: 10.1160/th04-10-0656
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of matrix metalloproteinases and their inhibitors in human and mouse lung development

Abstract: Lung development is a highly orchestrated process characterized by timed expression and activation of growth factor and protease/antiprotease systems. This interplay is essential in regulating vasculogenesis, alveolarization, and epithelial to mesenchymal transition during lung development. Alterations in the proteolytic/antiproteolytic balance of the lung have been associated with several respiratory diseases characterized by changes in the lung extracellular matrix (ECM). Here, we characterized the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 45 publications
(48 reference statements)
2
30
1
Order By: Relevance
“…Expression studies provide support for the expression of these toothrelated genes in other biomineralized tissues (22,33,34) (table S1). Similarly, MMP20 is located in one of the MMP gene clusters with several other matrix metalloproteinase genes, and its coexpression in nondental tissues (e.g., lung and large intestine) (21,35,36) with other MMPs may be attributed, in part, to gene expression neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies provide support for the expression of these toothrelated genes in other biomineralized tissues (22,33,34) (table S1). Similarly, MMP20 is located in one of the MMP gene clusters with several other matrix metalloproteinase genes, and its coexpression in nondental tissues (e.g., lung and large intestine) (21,35,36) with other MMPs may be attributed, in part, to gene expression neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal lung has a dominant proteolytic profile with high MMP-2, whereas the adult lung exhibits a more antiproteolytic profile with decreased MMP-2 (14). Thus, MMPs appear to play different roles in neonatal and adult hypoxia-induced pulmonary arterial remodeling.…”
Section: Mmp2mentioning
confidence: 99%
“…Other investigators (14,33) have evaluated MMP-2 in the developing lung during hypoxia. Gebb et al (33) showed that MMP-2 by zymography was lower at 3% compared with 21% O 2 in fetal rat lung explants despite no change in MMP-2 mRNA levels, indicating that hypoxia suppressed MMP-2 …”
Section: Mmp2mentioning
confidence: 99%
See 1 more Smart Citation
“…Remodelling of the extracellular matrix is a key feature of postnatal alveolar septation [24] with various matrix metalloproteinases (MMPs), zinc-dependent endopeptidases, involved [25,26]. Gelatinase A (MMP-2), gelatinase B (MMP-9) and macrophage metalloelastase (MMP-12) play a key role in emphysema development and progression [27][28][29].…”
mentioning
confidence: 99%